Systems Biology Modeling of the Complement System Under Immune Susceptible Pathogens - Zewde, Nehemiah T.; Hsu, Rohaine V.; Morikis, Dimitrios; Palermo, Giulia (Frontiers in Physics, 2021)
The complement system is assembled from a network of proteins that function to bring about the body’s first line of defense against invading pathogens. However, complement deficiencies or invasive pathogens can hijack complement to subsequently increase the body’s susceptibility to infections. What’s more, invasive pathogens are increasingly becoming resistant to the currently available therapies. Hence, it is important to gain insights into the highly dynamic interaction between complement and invading microbes in the frontlines of immunity. Here, we developed a computational model of the complement system composed of 670 ordinary differential equations with 328 kinetic parameters, which describes all three complement pathways (alternative, classical, and lectin) and includes description of mannose-binding lectin, collectins, ficolins, factor H-related proteins, immunoglobulin M, and pentraxins. Additionally, we incorporate two pathogens: (type 1) complement susceptible pathogen, (type 2) Neisseria meningitidis located in either nasopharynx or bloodstream. In both cases, we generate time profiles of the pathogen surface occupied by complement components and the membrane attack complex (MAC). Our model shows both pathogen types in bloodstream are saturated by complement proteins whereas MACs occupy <<1.0% of the pathogen surface. Conversely, MAC production in nasopharynx occupies about 1.5% to 10% of the total Neisseria meningitidis surface, thus making nasal MAC levels at least about eight orders of magnitude higher. As a result, the predicted complement-imbalance is associated with nasopharynx homeostasis, while the complement-balance may cause disruption to the nasopharynx homeostasis. This predicts rising nasal levels of complement regulators as early infection biomarkers for the Neisseria meningitidis disease. In summary, building on experimental literature data and available kinetic parameters, the model introduced here provides the basis for the computational prediction of the complement function under immune susceptible pathogens, and calls now for further application and for experimental validation.